Beethoven Studies 4 - Chapin, Keith; Wyn Jones, David (New York Cambridge University Press, 2020)
"Did you know that Beethoven contemplated, however fleetingly, writing more than forty symphonies and that for the Missa Solemnis he sought stimulus from a Latin-German dictionary? And what about the underappreciated sociable side of Beethoven's music to set alongside the familiar one of the heroic? Beethoven Studies 4 is a collection of ten chapters that approach the composer and his music from an appealing range of critical standpoints, aesthetic, analytical, biographical, historical and performance. Alongside essays that offer new information on Beethoven's compositional practice and broaden understanding of the music's contemporary and posthumous appeal, there are essays on his interaction with specific environments, Bonn and post-Napoleonic Austria, and vocal and piano performance practice. The volume will appeal to cultural historians and practitioners as well as Beethoven enthusiasts"--
From the Chapel to the Theatre to the Akademiensaal. Beethoven's Musical Apprenticeship at the Bonn Electoral Court, 1784-1792 / John Wilson -- Apprenticeship at the Bonn Electoral Court, 1784-1792 / John Wilson -- Gracious Beethoven? / W. Dean Sutcliffe -- Beethoven's Unfinished Symphonies / Barry Cooper -- Beethoven as Sentimentalist / Michael Spitzer -- Beethoven's Nature : Idealism and Sovereignty from an Ecological Perspective / Keith Chapin -- (Cross-)Gendering the German Voice / Katherine Hambridge -- Beethoven and tonal prototypes : an inherited and developing relationship / Giorgio Sanguinetti -- Shared identities and thwarted narratives. Beethoven and the Austrian Allgemeine musikalische Zeitung, 1817-1824 / David Wyn Jones -- Composing with a dictionary. Sounding the Word in Beethoven's Missa solemnis / Birgit Lodes -- Deafly Performing Beethoven's Last Three Piano Sonatas / Tom Beghin.
Includes bibliographical references and index.
Keywords: Beethoven, Ludwig van -- 1770-1827; 18th Century (1701-1800); 19th Century (1801-1900); Composer; Music education; Partimento; Music criticism; Mass; Keyboard music; Historically informed performance; Symphony; Bonn (Germany); Vienna (Austria)